2001
DOI: 10.1021/ac000906n
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Triazine Pesticides in Pure and Modified Subcritical Water

Abstract: Solubility measurements in pure and modified water serve as a basis for optimizing the subcritical water extraction of target analytes such as food contaminants. The solvent strength of the water is affected by both the system's temperature and the amount and type of cosolvent modifier that is added to the water, which causes a reduction in the dielectric constant of water. In the present work, the solubilities of the triazine pesticides atrazine, cyanazine, and simazine were measured in pure and modified wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…Ong and Len (2003) investigated the effect of the addition of ethanol (0 to 30%) into subcritical water on the extraction of berberine from a medicinal plant and found that the berberine content in the extracts increased with increasing amount of ethanol at treatment temperatures of 95 and 140℃ for 40 min. Modification of subcritical water with ethanol from 0 to 20% or urea at 28% (w/w) at 100℃ and 5 MPa increased the solubility of atrazine, a type of pesticide found in food commodities, from 500 to 6,000 mg/L (Curren and King, 2001). Choi et al (2003) applied subcritical water containing Triton X-100 at various concentrations above its critical micelle concentration to extract the pharmacologically active ingredients (ginsenosides) from the root of ginseng.…”
Section: Factors Affecting Extraction Efficiencymentioning
confidence: 99%
“…Ong and Len (2003) investigated the effect of the addition of ethanol (0 to 30%) into subcritical water on the extraction of berberine from a medicinal plant and found that the berberine content in the extracts increased with increasing amount of ethanol at treatment temperatures of 95 and 140℃ for 40 min. Modification of subcritical water with ethanol from 0 to 20% or urea at 28% (w/w) at 100℃ and 5 MPa increased the solubility of atrazine, a type of pesticide found in food commodities, from 500 to 6,000 mg/L (Curren and King, 2001). Choi et al (2003) applied subcritical water containing Triton X-100 at various concentrations above its critical micelle concentration to extract the pharmacologically active ingredients (ginsenosides) from the root of ginseng.…”
Section: Factors Affecting Extraction Efficiencymentioning
confidence: 99%
“…The dielectric constant of subcritical water decreases to match that of a polar organic solvent by increasing the temperature, 7) and a further decrease is achieved by adding an organic solvent, i.e., ethanol or acetone. 8) It has been reported that the lignocellulosic materials submitted to a subcritical organic solvent produced a black liquor which had radical scavenging ability. [9][10][11] Chiou et al have reported that subcritical aqueous ethanol and acetone were effective for extracting carbohydrates and phenolic compounds from rice bran.…”
mentioning
confidence: 99%
“…Solute solubility database and data correction Table 1 summarizes the solutes and solubility data sources [4][5][6][7][8][9][10][11][12][13][14] that were considered to derive an alternative correlation to Eq. (1) for the effect of system temperature on solute solubility [5] in liquid water, at the tabulated temperature and pressure ranges, and the units used to report the solute's solubility in water.…”
Section: Methodsmentioning
confidence: 99%
“…The starting point of our data correlation was a van't Hoff-type semi-logaritmic relationship for the solubility (x 2 ) versus the reciprocal of absolute temperature (T −1 ), as observed by Curren and King [7] for the solubility of triazine pesticides (atrazine, cyanazine, simazine) in HTW:…”
Section: Preliminary Data Analysismentioning
confidence: 99%